A snapshot of the main ownership features of the Slovenian corporate sector - Rojec, Matija (IB revija (Ljubljana), 2014)
A quarter of century since its transition began, Slovenia once again faces the task of implementing a comprehensive privatisation process if it is to reduce the level of state ownership and control in the corporate and financial sectors to an internationally comparable level. High ownership and corporate governance involvement on the part of the state in enterprises and financial institutions is a consequence of the Slovenian way of privatisation, a strong political preference for keeping a high level of state ownership in enterprises and financial institutions ('the national interest'), and of problems related to the economic recession in the corporate and financial sectors, with the former increasingly unable to service its debts to the latter. This paper takes a snapshot of the ownership structure and related trends in the Slovenian non-financial corporate sector in terms of majority SOEs, majority FOEs and majority DPOEs, with special attention given to SOEs. SOEs account for an important and increasing share of the Slovenian non-financial corporate sector, and they are heavily concentrated in the energy, transport and manufacturing sectors. They are the dominant players in the energy sector, are very important in the transport and communication sectors, but less so in the manufacturing sector. In 2008-2012, SOEs as a whole increased their importance to the Slovenian corporate sector in general, as well as in the majority of activity sections. In all the activity sections, SOEs are larger than average enterprises in the same sections, but in most sections they are less than average in terms of capital intensity, have lower sales per employee and lower export propensity, as well as lower levels of indebtedness. As a rule, SOEs do not perform as well as other types of enterprises in the same section of activity in terms of productivity, profitability and EBITDA. Their results are especially poor as far as operating profit is concerned, indicating that they have serious problems in their core operations.
Keywords: Enterprises; Podjetja; Privatisation; Privatizacija; Poslovna uspešnost; Success in business; Slovenia; Slovenija; lastništvo; lastniška struktura